(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Emergence of resistant strains of staphylococcus aureus, namely methicillin-resistant S. Aureus (mrsa) in all levels of urban and rural societies has become a haunting problem for the recent world. Objectives: This study assesses and explores the transfer of resistant Staphylococcus aureus bacteria in certain high social class of community focusing on nail as reservoir for transmitting the infection. Methods: One hundred swabs taken from nails were collected from college students in Malaysia. Assays for identification and differentiating Staphylococcus aureus were conducted to identify target bacteria. Moreover, this study compared the efficacy of the different identification tests with gold standard, PCR assay. The tests used were tube coagulase, DNase agar test, antibiogram, several routine biochemical identification tests and PCR assays. PCR assay used specific primers for resistance or species-related genes: mecA, ermA, ermB, ermC, msrA, linA, femA, and nuc genes. Results: A total of 155 bacterial isolates were isolated from college students’ nails, non-PCR assays of identification and resistance detection revealed presence and spread of MRSA in nails of 3 college students. PCR-amplification of the nuc gene was used as a baseline test to detect Staphylococcus aureus. 20 isolates were detected as Staphylococcus aureus using traditional tests while PCR showed only 4 isolates are S. aureus, only 3 of them are MRSA. Sensitivity of antibiogram ranged from 88.9 to 100% but its specificity was very low (0-100%). For tube coagulase, sensitivity was 36.4-100%) while specificity was also not so high (66.7-100%). Conclusion: Collectively, nails proved to have potential for the transfer of MRSA in community of college students in South East Asia. Moreover, PCR assay for identification of S. aureus resistance proved to be superior on other methods. Keywords:Staphylococcus aureus, MRSA, PCR, antibiotic resistance